Chlordane components and metabolites in seven species of Arctic seabirds from the Northwater Polynya: Relationships with stable isotopes of nitrogen and enantiomeric fractions of chiral components - Fisk, A. T.; Moisey, J.; Hobson, K. A.; Karnovsky, N. J.; Norstrom, R. J. (Environmental Pollution, 2001)
The Northwater Polynya (NOW) is a large area of year-round open water found in the high Arctic between Ellesmere Island and Greenland. NOW has high biological productivity compared with other arctic marine areas, and supports large populations of several seabird species. Seven species of seabirds, dovekie (Alle alle, DOVE), thick-billed murre (Uria lomvia, TBMU), black guillemot (Cepphus grylle, BLGU), black-legged kittiwake (Rissa tridactyla, BLKI), ivory gull (Pagophila eburnea, IVGU), glaucous gull (Larus hyperboreus, GLGU) and northern fulmar (Fulmaris glacialis, NOFU) were collected in May and June 1998 to determine chlordane concentrations in liver and fat and to examine species differences, relationships with stable isotopes of nitrogen, and enantiomeric fractions (EFs) of chiral components. ΣCHLOR concentrations varied over an order of magnitude among species, from a low of 176±19 ng/g (lipid corrected) in TMBU liver to a high of 3190±656 ng/g (lipid corrected) in NOFU liver. Lipid-corrected concentrations of chlordane did not vary between sex for any species or between fat and liver except for the DOVE, that had fat concentrations that were significantly greater than the liver. δ15N values described a significant percentage of the variability of concentrations for most chlordane components, although less than what has been reported for whole food chains. Slopes of δ15N versus concentration of chlordane components and ΣCHLOR were similar with the exception of those which were metabolized (trans-chlordane) or formed through biotransformation (oxychlordane). The relative proportions of chlordane components in seabirds were related to phylogeny; the procellariid (NOFU) had the greatest percentage of oxychlordane (>70%), followed by the larids (BLKI, IVGU and GLGU; 40-50%) and the alcids (DOVE and BLGU; 10-20%). The exception was TBMU, an alcid, where oxychlordane made up >40% of its chlordane. EFs of chiral components failed to predict concentration or trophic level, but did identify biotransformation ...